2007
DOI: 10.1097/01.coc.0000251398.57630.4f
|View full text |Cite
|
Sign up to set email alerts
|

The Rates of Chemotherapy-Induced Amenorrhea in Patients Treated With Adjuvant Doxorubicin and Cyclophosphamide Followed by a Taxane

Abstract: Older age and the addition of taxane to AC increased the risk of CIA and the amenorrhea was more likely to be irreversible for women >40. Women < or =40 often resume menstruation even after 6 months of amenorrhea, and the addition of T does not play a role. Subsequent resumption of menstrual function must be considered when initiating appropriate hormonal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 16 publications
5
94
1
8
Order By: Relevance
“…Fornier et al 17 reported that the incidence of long-term (Q12 mo) amenorrhea in young women (G40 y) was 15% when treated with adjuvant anthracycline and taxane-containing chemotherapy: 13% with tamoxifen and 17% without tamoxifen. Tham et al 18 showed that the overall rate of CRA in women who received AC followed by a taxane was 64% compared with 55% with AC alone (P = 0.21). Rates of CRA were higher in older women (940 y) (82% vs 55%, P = 0.004).…”
Section: Factors Associated With Permanent Cramentioning
confidence: 99%
“…Fornier et al 17 reported that the incidence of long-term (Q12 mo) amenorrhea in young women (G40 y) was 15% when treated with adjuvant anthracycline and taxane-containing chemotherapy: 13% with tamoxifen and 17% without tamoxifen. Tham et al 18 showed that the overall rate of CRA in women who received AC followed by a taxane was 64% compared with 55% with AC alone (P = 0.21). Rates of CRA were higher in older women (940 y) (82% vs 55%, P = 0.004).…”
Section: Factors Associated With Permanent Cramentioning
confidence: 99%
“…Younger women often resumed menstruation months after treatment was completed and this again demonstrates that age is one of the strongest predictors that a women will experience chemotherapy-induced amenorrhoea. 25 The addition of traztuzumab to standard chemotherapy does not appear to have any additional effect on POF above that of the chemotherapy alone. 35 This technology has been used in Israel, where the rates of…”
Section: Young Women With Cancermentioning
confidence: 95%
“…Fertility outcomes after common adjuvant chemotherapy regimens for breast cancer by major clinical studies are presented in Table 1 [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Endocrine Therapymentioning
confidence: 99%